Upaya Pencegahan Risiko Komplikasi Kegawatdaruratan Hipertensi melalui Metode Fast di Kelurahan Legok Kota Jambi - Muhammad Hidayat; Hesty Hesty; Maimaznah Maimaznah; Iin Indrawati; Vevi Suryenti Putri (3031-8572, 2025)
Severe increase in blood pressure (BP) (>180/120 mm Hg) accompanied by evidence of new damage or worsening target organ damage can trigger the risk of hypertension emergency complications, one of which is stroke. This community service activity was carried out in Legok Village, Jambi City. The implementation method was survey, observation, interview, discussion, and demonstration through health education. Based on field observations, most people did not know the efforts to prevent the risk of hypertension emergency complications through the fast method. This activity was attended by 18 people from RT 01, Legok Village, Jambi City. Based on the initial survey, the partner problem was found to be the problem of knowledge. The purpose of this education is to change knowledge, attitudes and actions of the community regarding efforts to prevent the risk of hypertension emergency complications through the fast method through group education for the community (adolescents-elderly). The results of this activity were that participants correctly answered questions about hypertension prevention, applied the principles of preventing the risk of complications in hypertension emergencies using the FAST method, and were able to develop preventive activities for hypertension emergencies using the FAST method. In conclusion, there was an increase in public knowledge about the importance of preventing the risk of complications in hypertension emergencies using the FAST method in their respective homes.